Stock Returns and Volatility: A Study of the Nepal Stock Market - Thapa, Narad Kumar (Nepal Journal of Multidisciplinary Research, 2023)
The study shows the relationship between volatility and stock return for the NEPSE Index and NEPSE banking stocks. In this study, the NEPSE index and banking stock index were used to compare the risk-return trade-offs between the NEPSE index with the ADBL Bank and NBL Bank in Nepal. Secondary data are the major sources of information and the data were obtained from the NEPSE website over 5-years period, from 2018 to 2022. In this study, beta coefficients were calculated, indicating that both banks are perceived to have lower systematic risk than the overall stock market. This suggests that these banks are relatively less exposed to market volatility. The study will be useful for investors evaluating the safety of government bank stocks as an investment. Furthermore, this research is anticipated to offer valuable perspectives to investors assessing the security and appeal of government bank stocks as a potential investment. It not only illuminates the risk-return characteristics of these stocks but also acts as an informative guide for investors seeking to make well-informed choices in the Nepalese stock market.